Heat treatment and microbial digestion of poulty feather for biogas production - Mézes, Lili; Bíró, Tibor; Tamás, János; Petis, Mihály (Acta Agraria Debreceniensis, 2007)
The aim of this research was the elaboration of the technological parameters of heat pre-treatment and microbial digestion of poultry feathers for biogas production. Feathers were treated at 70, 100, 140 °C, and subsequently digested by Bacillus licheniformis, or keratin disintegrator bacteria. Investigations focused on the optimalization of parameters influencing poultry feather biodegradation. The optimal range of pH, temperature, feather size and bacillus:feather ratio were determined in the experiments, as well as the analysis of relationship between the examined parameters. In order to be able to track the dynamics of the biodegradation, we determined the extinction level of the liquid phase of the biodegraded material in the different experimental treatments. The results showed that the rate of hydrolysis was significantly higher in the treatments with bacteria than in the treatments without it. Regarding the pretreatments at 70, 100 and 140 °C, the digestion of feather was the most intensive at 70 °C. The most extensive digestion was observed in case of 1:3 feather:water ratio. The highest intensity of feather digestion was detected in the treatment with 1% microbe ratio.